TIME-DEPENDENT BEHAVIOR OF ELECTROMAGNETIC AND ACOUSTIC EMISSION AS PREDICTOR OF INSTABILITY OF CONTACTS BETWEEN BLOCKS - Sobolev G.A.; Demin V.M. (My University, 1988)
Electromagnetic emission from rocks is useful in prediction of earthquake and rock bursts. We investigated electromagnetic (EME) and acoustic emission (AE) on a concrete model consisting of three blocks. Based on our measurements of stresses, strains, acoustic and electromagnetic emission, as well as on the results of earlier investigations, we offer an explanation of the energy liberation via acoustic and electromagnetic emission. The recorded times of emission and the shapes of the individual acoustic and electromagnetic emission signals indicate that the EME signals are produced simultaneously with the brief (<500 μsec) acoustic emission. But longer acoustic emission (1 msec or more) is in most cases not accompanied by electromagnetic emission.